A lira hesitante de Ana Cristina Cesar - FERRO, Letícia Costa e Silva (2010)
Once in contact with contemporary poetry, we can think of its multiple practice in which form and diction, the most diverse ones resist to critical reception that are tied to established literary standards. The literary work of Ana Cristina Cesar can be included in this particular context. Controversial in its essence, her work keeps oscillating and drifting from stable matters. Therefore, the aim of this study is to read it by the bias of hesitation, between poetry and prose, center and edge, biography and fiction, memory and forgetfulness, in order to find out what is hidden underneath it, and whether it means simulation or dissimulation. The essay is elected then, in the wake of Adorno (2003), as the academic style of dissertation. It is a belief that the essay is analogous to the poetry studied, for it is placed among absurdities since it neither starts from a very beginning nor converges at a final ending.